PENYULUHAN UPAYA PENINGKATAN KREATIVITAS PEMUDA UNTUK MEMPERSIAPKAN DIRI MENJADI MAHASISWA SEKALIGUS WIRAUSAHA - Herlina, Herlina; Melina, Erny; Agustinus Sitanggang, Prayetno; Bestary Al Haitamy, Eri; Asmaida, Asmaida (Bersama : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service aims to increase knowledge about efforts to increase creativity in preparing themselves to become students and entrepreneurs for young people in Tantan Village who want to continue their education at university. The methods used in this service are lectures and discussions. The stages start from coordinating with village youth and village officials, outreach activities, and the evaluation stage. The discussion stage showed that the participants were ready to become students and entrepreneurs through creative abilities by the characteristics of a creative person.